DALI: A Methodology for the Co-Design of Dataflow Applications on Hardware/Software Architectures - Véstias, Mário P.; Neto, Horácio C. (16th Brazilian Symposium on Integrated Circuit Design (SBCCI 2003), 2003)
The design of dedicated systems is being subject to severe cost, performance, time-to-market and flexibility constraints.So, it is becoming a quite complex process.This paper proposes a system-level methodology to help in the design of dedicated architectures, possibly with both hardware and software components, for dataflow-dominatedapplications. The methodology helps the designer to find the best architecture for a particular customer's specification.The potential of the proposed methodology is illustrated with the design of a system for video encoding.